2004
DOI: 10.3390/90600480
|View full text |Cite
|
Sign up to set email alerts
|

Self-Terminating, Oxidative Radical Cyclizations

Abstract: The recently discovered novel concept of self-terminating, oxidative radical cyclizations, through which alkynes can be converted into carbonyl compounds under very mild reaction conditions using O-centered inorganic and organic radicals as oxidants, is described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Alkoxyl radicals can be generated from peroxyl radicals via tetroxides or one-electron reduction of alkyl hydroperoxides [36]. Alkoxyl radicals undergo rapid addition and hydrogen abstraction reactions, as well as unimolecular fragmentation and rearrangements [37]. Most primary and secondary alkoxyl radicals undergo a rapid 1,2-hydrogen shift, which results in the formation of α-hydroxyalkyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Alkoxyl radicals can be generated from peroxyl radicals via tetroxides or one-electron reduction of alkyl hydroperoxides [36]. Alkoxyl radicals undergo rapid addition and hydrogen abstraction reactions, as well as unimolecular fragmentation and rearrangements [37]. Most primary and secondary alkoxyl radicals undergo a rapid 1,2-hydrogen shift, which results in the formation of α-hydroxyalkyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Future work will also focus on using computational methods to gain additional theoretical insights into the driving forces of the diastereoselection process in 5-exo cyclizations of such highly substituted radicals, the role of the geometry at the radical centre and the α nitrogen (e.g., planar or sp 3hybridized), and the possible influence of complexation to Ce III/IV in the transition state. [7,29] The nearly entirely different behaviour of the triflatesubstituted alkyne 15 compared to the tosylated derivatives 14 shows that, besides the substitution pattern at nitrogen, the conformation of the starting materials must also be considered. Compound 15 exists at room temperature as an equilibrium of two conformers (the reason for this is not clear), whereas 14 is conformationally pure.…”
Section: Discussionmentioning
confidence: 99%
“…[5] We have meanwhile demonstrated that this type of self-termination is a very general concept in radical chemistry, and many different inorganic, organic, uncharged, and even charged O-centred radicals can act, similar to NO • 3 , as O-atom donors in their reactions with alkynes. [6] Both experimental [4] and theoretical investigations [7] have revealed that the 1,5-HAT is the rate-limiting step in this sequence, whereas the diastereoselectivity is likely determined in the subsequent 5-exo cyclization of radical intermediate 4. Besides the size and stereochemistry (cis or trans) of the fused cycloalkane ring, it was found that both absence or presence of the heteroatom (X = O) as well as the nature of the substituent R influenced the diastereoselectivity of this cyclization step.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wille and coworkers have described a collection of innovative new transformations that they have classed as "self-terminating radical reactions" [ 5 - 10 ]. For example, addition of broad assortment of oxygen-centered radicals to cyclodecyne 1 provides isomeric ketones 2 (major) and 3 (minor) in variable yields, depending on the specific radical involved and the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%